Gambaran Tingkat Pengetahuan Penggunaan Obat Tetrasiklin Tanpa Resep Dokter di Kelurahan Bangselok Kabupaten Sumenep - Aldita Cahyani Puspitasari; N A Ashari Putri; Moch Rizal Ardiansyah; Rizdyana Firmaniar; Zakiyyah Qurrotul ‘Aini (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background : Lack of public understanding and knowledge regarding the correct and appropriate use of antibiotics is one of the factors that triggers antibiotic resistance. Tetracycline is the antibiotic most frequently used by the public. Based on its mechanism of action, tetracycline is included in the class of bacteriostatic antibiotics which work by inhibiting bacterial growth. Inappropriate use of tetracycline drugs can trigger resistance to tetracycline drugs. Purpose: The aim of this research is to find out the level of knowledge about the use of tetracycline drugs purchased without a doctor's prescription in Bangselok sub-district. Method : This research was used the quantitative which is using the observational study approach. Total respondent were used in this are 98 peoples. Analysis in this study used descriptive. Result : there ware 55 respondent (56,1%) had good knowledge, 20 respondent (20,4 %) had sufficient knowledge, and 23 (23,5%) had lack of knowledge. Conclusion : The level of community knowledge in Bangselok sub-district is good.